Angiographic and Optical Coherence Tomography Insights Into Bioresorbable Scaffold Thrombosis. (May 2015) - Karanasos, Antonios; Van Mieghem, Nicolas; van Ditzhuijzen, Nienke; Felix, Cordula; Daemen, Joost; Autar, Anouchska; Onuma, Yoshinobu; Kurata, Mie; Diletti, Roberto; Valgimigli, Marco; Kauer, Floris; van Beusekom, Heleen; et al.
<x xml:space="preserve">Abstract</x> Background— As bioresorbable vascular scaffolds (BVSs) are being increasingly used in complex real-world lesions and populations, BVS thrombosis cases have been reported. We present angiographic and optical coherence tomography (OCT) findings in a series of patients treated in our center for definite bioresorbable scaffold thrombosis. Methods and Results— Up to June 2014, 14 patients presented with definite BVS thrombosis in our center. OCT was performed in 9 patients at the operator's discretion. Angiographic and OCT findings were compared with a control group comprising 15 patients with definite metallic stent thrombosis. In the BVS group, time interval from index procedure to scaffold thrombosis ranged from 0 to 675 days. Incomplete lesion coverage by angiography was identified in 4 of 14 cases, malapposition by OCT in 5 of 9 cases, strut discontinuity in 2 of 9 cases, and underexpansion in 2 of 9 cases. Five patients had discontinued dual antiplatelet therapy, and in 3 of them discontinued dual antiplatelet therapy discontinuation had occurred the week preceding the event. There were no significant differences in angiographic or OCT findings between BVS and metallic stent thrombosis. Conclusions— Suboptimal implantation with incomplete lesion coverage, underexpansion, and malapposition comprises the main pathomechanism for both early and late BVS thrombosis, similar to metallic stent thrombosis. Dual antiplatelet therapy discontinuation seems to also be a secondary contributor in several late events. Our observations suggest that several potential triggers for BVS thrombosis could be avoided.